Evaluasi Program Kerja KKN: Tantangan dalam Pengabdian Masyarakat di Desa Tawang Rejo - Herlanda, Iben; Adiyat, Rahman; Fitalia, Rosi; Depitrieni, Rindri; Bunga, Windy Sintia; Popitasari, Meri; Febrianti, Jeni; Sara, Ani; Susanti, Soneta Rahma; Zikri, M (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This article discusses the evaluation of the Real Work Lecture (KKN) work program carried out in Tawang Rejo Village, focusing on the challenges faced in community service. KKN is a form of service that aims to empower the community through various programs that involve active participation of residents. Through qualitative research, this article tries to understand and analyze the various challenges and obstacles faced by the KKN group in implementing our Work Program. In Tawang Rejo Village, KKN students face various challenges, such as lack of participation from the community, budget limitations, time limitations and having to adapt to different surrounding environments. This evaluation is expected to provide recommendations for future improvements in the KKN program, so that community service can be more effective and sustainable.